FEATURES OF PERFORMANCE MEASUREMENT SYSTEMS IN TUNISIAN SMES: RESULTS OF AN EMPIRICAL STUDY - Ghrairi, Dr. Abdelmonem (The journal of contemporary issues in business and government, 2021)
Evolving in a globalized economy and facing increasing pressure from their business partners, Tunisian SMEs are facing new challenges in managing their performance. To meet these challenges, Tunisian SMEs must adopt management tools that allow them to maintain the excellence they need, i.e., tools that measure their performance in a multidimensional, efficient and effective manner. However, this need to measure and manage performance facesan absence of tools adapted to this type of companies that take into account both their limited resources and their expertise to be able to use them effectively. Furthermore, in recent years the evolution of management control systems has resulted in the questioning of the relevance of financial measures as representative of business success and the diffusion of performance measurement systems designed to take into account different complementary strategic perspectives. Developed for large firms, the approaches advocated would be incompatible with the practice of performance measurement in small firms (Hudson, Smart and Bourne, 2001). The paucity of empirical research on performance measurement systems in SMEs has been highlighted by many studies. Lack of knowledge about performance measurement systems developed in SMEs invites the study of the features of these systems in this type of businesses. This study also contributes to documenting the specific problem of performance measurement systems in SMEs. Using the results of an empirical study based on a quantitative survey of 57 Tunisian companies, this paper analyzes the features of performance measurement systems implemented in small and medium-sized enterprises and shows the diversity of practices of SMEs. This study provides Tunisian SMEs managers and advisors with an empirical framework for the design, improvement and evaluation of performance measurement systems.